Maternal Stress in Gestation: Birth Outcomes and Stress-Related Hormone Response of the Neonates - Qian Su; Huifang Zhang; Yanyan Zhang; Huiping Zhang; Ding Ding; Junan Zeng; Zhongliang Zhu; Hui Li (Elsevier, 2015)
Relatively few studies have been made on neurobehavioral outcomes of prenatal maternal stress during the newborn period, and little research has focused on umbilical cord stress hormones including cortisol, adrenocorticotropic hormone (ACTH), norepinephrine, and epinephrine. Our objective was to investigate the effects of prenatal maternal life stressors on neonatal birth outcomes, neurobehavioral development, and stress-related hormones levels. Methods: Participants were 142 mothers and their infants; 71 were selected as the prenatal life stressor exposed group and 71 as the control group matched on maternal age, gestational week, delivery type, socioeconomic and education status, and newborns' sex. Maternal life stressors during pregnancy were determined using the Life Events Scale for Pregnant Women. Neonatal neurobehavioral development was assessed with the Neonatal Behavioral Neurological Assessment. Umbilical cord plasma stress-related hormones, including ACTH, cortisol, norepinephrine, and epinephrine were measured using an enzyme-linked immunosorbent assay. Results: In the prenatal life stressors exposed group, newborns had significantly lower birth weight, smaller head circumference (p < 0.01, p < 0.01, respectively). Scores of Neonatal Behavioral Neurological Assessment were significantly reduced (p < 0.001). Cord plasma ACTH, norepinephrine, and epinephrine levels were significantly increased (p < 0.001), but cortisol levels were reduced (p < 0.001). Conclusion: Prenatal maternal stress may negatively affect fetal birth outcomes, neurobehavioral development and affect neonates' cord plasma ACTH, cortisol, norepinephrine, and epinephrine.